Oral injuries associated with the use of dental prostheses: a literature review (Research, Society and Development, 2021)
Despite advances in Dentistry, there is still an incidence of tooth loss, especially in the elderly, constituting a public health problem. One of the important instruments for oral rehabilitation is the prosthesis, which aims to rehabilitate edentulous areas. The consequences of inadequate use and poor hygiene of removable dentures can affect the oral cavity due to the accumulation of microorganisms or arising from a poor adaptation, causing trauma to the alveolar ridges. Thus, the aim of this study is to highlight the main injuries that affect the oral cavity resulting from poor adaptation and poor hygiene. The study is a narrative literature review, developed through a survey in the electronic databases PubMed, Scholar Google and SciELO. The search strategy was carried out through the DeCs “Dental prosthesis”, “Oral manifestations” and “Lesions”, in English, Spanish and Portuguese. As eligibility criteria, 20 articles were selected that have a theme compatible with the proposed objectives of this work, excluding all others. Negligence with the hygiene of the prosthesis or poor adaptation can cause oral injuries, since it is a favorable environment for the proliferation and survival of oral microorganisms and biofilm formation. Among the most common pathologies, we can highlight: inflammatory hyperplasia, traumatic ulcer, angular cheilitis and prosthetic stomatitis. It is concluded that the prosthesis is important to rehabilitate edentulous patients who have lost their essential functions. However, follow-up and good instruction from the dentist on oral hygiene is essential, in addition to an adequate adjustment of the prosthesis.